Galectin-8 deficiency promotes chronic splenomegaly persistence in Chagas disease - Bertelli, Adriano (2025)
Galectins (Gals) are mammalian lectins with affinity for b-galactosides, whichdrive the immune response through several mechanisms. The specific role ofGal-8 in the development of inflammation remains controversial, as it has beenshown to induce either T cell proliferation or regulation in different models.During the acute phase of Trypanosoma cruzi infection, a characteristicsplenomegaly is induced that is associated with both antigen-specific andnon-specific polyclonal lymphocyte proliferation. This splenomegaly resolvesas the infection transitions to the chronic phase. While the pathogenesis ofChagas disease is not yet fully understood, it is widely accepted to involve bothparasite persistence and the host immune response. In this study, C57BL/6J andGal-8-deficient (KO) mice infected with the Ac strain were analyzed during thechronic phase (4 months post-infection). Notably, infected Gal-8KO mice failedto resolve the T. cruzi-induced acute phase splenomegaly. Despite this,parasitemia, spleen parasite load, and survival rates were comparable betweenthe two groups, suggesting that Gal-8 is not involved in parasite control. Theobserved differences in spleen cellularity were primarily attributed to Tlymphocyte proliferation, while B cells exhibited no significative changes intotal cell number, proliferation levels and production of total and parasitespecific antibodies. Overall, our results reveal that Gal-8 plays an antiinflammatory role during chronic T. cruzi infection and is critical in controllingsplenomegaly, a process for which no associated regulatory molecules havebeen identified to date.